An improved algorithm to compute the ω-primality - Achour, Wissem; Chaabane, Djamal; Blanco, Víctor (Optimization letters, 2021)
In this paper, we present an improved methodology to compute the ω -primality of a numerical semigroup. The approach is based on exploiting the structure of the problem on a resolution method for optimizing a linear function over the set of efficient solutions of a multiple objective integer linear programming problem. The numerical experiments show the efficiency of the proposed technique compared to the existing methods.